2016
DOI: 10.1111/jace.14568
|View full text |Cite
|
Sign up to set email alerts
|

Broadband NIR photoelectronic performance for sunlight‐induced photocurrent from (NaYF4:Yb‐Er)/BiOI hybrid films

Abstract: The fabrication and near‐infrared optoelectronic performance of the (NaYF4:Yb‐Er)/BiOI upconversion phosphor/semiconductor hybrid films are reported. The composite films were fabricated by a simple electro‐deposition and successive ionic layer adsorption and reaction (SILAR) method. We observed efficient upconversion emissions in the film of NaYF4:Yb‐Er upon irradiation by near‐infrared part of simulated sunlight, and the UC emission is drastically quenched in the composite film (NaYF4:Yb‐Er)/BiOI. More import… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(3 citation statements)
references
References 39 publications
0
3
0
Order By: Relevance
“…Figure C shows the up‐conversion spectrum of PL spectrum of BiOBr:Yb,Er and Bi/BiOBr:Yb,Er/C under 980 nm excitation. For BiOBr:Yb,Er, characteristic peaks at 660, 545, and 525 nm are observed and can be assigned to 4 F 9/2 → 4 I 15/2 , 4 S 3/2 → 4 I 15/2 , and 2 H 11/2 → 4 I 15/2 transitions of Er 3+ , respectively, indicating the successful up‐conversion of 980 nm to visible light. However, the 545 and 525 nm emissions in Bi/BiOBr:Yb,Er/C are significantly suppressed.…”
Section: Resultsmentioning
confidence: 96%
“…Figure C shows the up‐conversion spectrum of PL spectrum of BiOBr:Yb,Er and Bi/BiOBr:Yb,Er/C under 980 nm excitation. For BiOBr:Yb,Er, characteristic peaks at 660, 545, and 525 nm are observed and can be assigned to 4 F 9/2 → 4 I 15/2 , 4 S 3/2 → 4 I 15/2 , and 2 H 11/2 → 4 I 15/2 transitions of Er 3+ , respectively, indicating the successful up‐conversion of 980 nm to visible light. However, the 545 and 525 nm emissions in Bi/BiOBr:Yb,Er/C are significantly suppressed.…”
Section: Resultsmentioning
confidence: 96%
“…Many researchers investigated the effects of doping and film thickness on the photoresponse and photodetection of various materials in the UV to NIR domains. [ 130–136 ] Fang et al. reported the effect of layering dynamics on the optical response of graphene.…”
Section: Challenges and Future Trendsmentioning
confidence: 99%
“…[129] Many researchers investigated the effects of doping and film thickness on the photoresponse and photodetection of various materials in the UV to NIR domains. [130][131][132][133][134][135][136] Fang et al reported the effect of layering dynamics on the optical response of graphene. [137] The constant movement of the zero-cross point in the intricate optical conductivity's imaginary component, which is made possible by an increase in thickness, is what gives graphene its adjustable optical responsiveness.…”
Section: Layering Dynamics In Photodetectorsmentioning
confidence: 99%